As culturas dos cuidados maternos: do rádio às mídias digitais - Maia, Carolina Cardinal Duarte Campaña (2022)
This theoretical work aimed to analyze the current culture of maternal care and the one that prevailed at the time when Winnicott spoke on the radio to mothers at BBC London. Initially, we contextualize the interlocutor in the culture of radio in post-World War II England. We describe the contemporary digital media culture, demonstrating its functioning and its repercussions on the behavior of the contemporary subject. Then, we analyzed Winnicott´s radio talks addressed to mothers between 1939 and 1965 and excerpts from speeches of a digital medium known as ‘Ohana Materna’, from 2019 to 2021. At the end, we point out some differences in relation to the mentioned cultures and a possible therapeutic intervention was proposed for mothers who take care of their children